Volumetric comparison of mandibular condyles and mandibles in the different skeletal classes in the Saudi population - Hussain Y. A. Marghalani (PeerJ, 2024)
Background Assessing the relationship between the condyle and mandible volume and the various skeletal classes is essential in orthodontic diagnosis. The current study evaluated this relationship using volumetric cone-beam computed tomography (CBCT), cephalometric methods, and the correlations between them. Materials and Methods The study examined 37 full-head CBCTs (74 condyles) from adults in the Saudi population. The condyle and mandible were separated from within the CBCT images. The volume of each segment was compared to measurements from multiple cephalometric analyses. Results The combined total condylar volume has a moderate correlation with the maxillomandibular differential in each of the genders and in the total sample. Mandibular volume has a significant correlation with the Wits appraisal (sagittal classification) in males. It was also significantly correlated with the vertical classification using gonial angles in females and in the total sample. Conclusion The relationship between mandible and condyle volume and cephalometric measurements is both dimensional and within the maxillomandibular complex rather than positional or related to the cranial base. Also, the correlation between the condylar and mandibular volumes and the sagittal and vertical dimensions in the orthodontic skeletal classes provides better insight into the mandibular complex.